2016
DOI: 10.5742/mewfm.2015.92792
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Measles , Rubella , Mumps and Varicella Specific Antibodies in Primary School Children

Abstract: Measles, mumps, rubella and varicella are diseases that are tracked by the World Health Organization (WHO) as common and serious vaccine-preventable diseases. Aim of the Work: To evaluate the immune status and susceptibility against measles, mumps, rubella, and varicella in primary school children and to study the effects of some sociodemographic factors on the seroprevalence. Subjects and methods: This is a cross-sectional study conducted on 180 children. All children included in this study were subjected to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 3 publications
0
7
0
1
Order By: Relevance
“…This may be due to the older age group of our participants ranged from 15 to 43 years old who became immune due to previous VZV infection or contact in our overpopulated country. A recent study conducted on Egyptian primary school children has reported VZV seroprevalence to be 38.9% and correlated increasing VZV antibodies with increasing age [21].…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the older age group of our participants ranged from 15 to 43 years old who became immune due to previous VZV infection or contact in our overpopulated country. A recent study conducted on Egyptian primary school children has reported VZV seroprevalence to be 38.9% and correlated increasing VZV antibodies with increasing age [21].…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to the vaccination schedule or changes in maturing immune systems [26]. A study in Pakistan found that the levels of the measles-specific IgG antibody increased from 60.0% to 84.62% in children aged 9 months to 5 years [36].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the seroprevalence of the measles antibody in northwest China was lower than in other Chinese regions, such as Jiangsu (97.6%) [ 9 ], Tianjin (97.5%) [ 25 ], and Zhejiang (96.5%) [ 10 ] in southern China. The regional variation in measles seropositivity, both within China and across nations, might be due to differences in the design of early childhood immunization programs in each region [ 26 ] and inherited differences among various populations [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our measles IgG value is quite similar to that found in the seroprevalence study of the measles IgG antibody in 1- to 5-year-old children in Zaria, Northwestern Nigeria, which reported a prevalence of 47.80% [ 18 ]. This variation (both local and national) is likely due to differences in individual immune responses, differences in the design of immunisation programs, or both [ 19 ], [ 20 ].…”
Section: Discussionmentioning
confidence: 99%